2013
DOI: 10.4082/kjfm.2013.34.3.199
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic Fatty Liver Disease and Chronic Kidney Disease in Koreans Aged 50 Years or Older

Abstract: BackgroundNon-alcoholic fatty liver disease (NAFLD) and chronic kidney disease (CKD) share common pathogenic mechanisms and many risk factors, and both are linked to an increased risk of cardiovascular diseases. The aim of this study was to assess the association between NAFLD and CKD according to the presence of hypertension and diabetes mellitus in Koreans aged 50 years or older.MethodsA cross-sectional study of 1,706 subjects who received their routine health examination was conducted between May 2008 and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…Individuals with NAFLD can progress to develop cirrhosis and hepatocellular carcinoma and are also at risk for extrahepatic diseases including diabetes mellitus and cardiovascular disease . Further, emerging evidence suggests NAFLD may be associated with chronic kidney disease (CKD) . CKD represents a substantial disease burden in the United States, affecting approximately 8% of the population, and the incidence is increasing in parallel to obesity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with NAFLD can progress to develop cirrhosis and hepatocellular carcinoma and are also at risk for extrahepatic diseases including diabetes mellitus and cardiovascular disease . Further, emerging evidence suggests NAFLD may be associated with chronic kidney disease (CKD) . CKD represents a substantial disease burden in the United States, affecting approximately 8% of the population, and the incidence is increasing in parallel to obesity .…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic steatosis has been associated with CKD in a number of prior cross‐sectional and longitudinal studies, though results are conflicting . Recent meta‐analyses have concluded that NAFLD was associated with an increased risk of prevalent and incident CKD, and the severity of liver disease positively correlated with advancing CKD .…”
Section: Introductionmentioning
confidence: 99%
“…In the last 5 years, a number of cross-sectional community-based and hospital-based studies have consistently demonstrated that NAFLD, as diagnosed either by imaging [16][17][18][19][20][21][22][23][24] or by histology [25][26][27][28][29] , is associated with an increased prevalence of CKD (defined as presence of decreased estimated glomerular filtration rate [eGFR] or abnormal albuminuria or overt proteinuria) in patients with NAFLD. In these studies, the prevalence of CKD in patients with NAFLD ranged from approximately 20% to 55% compared to 5%-30% in those without NAFLD [16][17][18][19][20][21][22][23][24][25][26][27][28][29] .…”
Section: Epidemiological Studies Linking Nafld To Risk Of Ckdmentioning
confidence: 99%
“…In these studies, the prevalence of CKD in patients with NAFLD ranged from approximately 20% to 55% compared to 5%-30% in those without NAFLD [16][17][18][19][20][21][22][23][24][25][26][27][28][29] . Notably, in most of these studies the association between NAFLD and CKD was independent of common cardio-renal risk factors across a wide range of patient populations.…”
Section: Epidemiological Studies Linking Nafld To Risk Of Ckdmentioning
confidence: 99%
“…Because of study population heterogeneity, and differences in NAFLD diagnostic features, NAFLD severity, and CKD definition used, the reported prevalence and incidence of CKD are largely conflicting. However, most of the recent large population based andhospital based studies represent that the prevalence and incidence of CKD was greatly increase in subjects with NAFLD [39][40][41][42][43][44]. According to a current metaanalysis,NAFLD was connected with an raised prevalence and incidence of CKD and nonalcoholic steatohepatitis(NASH) was related with a higher prevalenceand incidence of CKD than simple steatosis independent of potential confounding factors including age, smoking, obesity, hypertension, and metabolic syndrome elements [45].…”
Section: Chronic Kidney Disease and Nafldmentioning
confidence: 99%